Russia, Oriente slavo e Occidente europeo. Fratture e integrazioni nella storia e nella civiltà letteraria Fratture e integrazioni nella storia e nella civiltà letteraria - Delaunay, Claire; Priadko, Eugène; Pieralli, Claudia (Biblioteca di Studi Slavistici, 2017)
The present book addresses a wide range of problems concerning the history of Eastern Slavic culture in its interaction with cultural models of Western Europe. This collective work is the final result of the French-Italian conference "Fratture e integrazioni tra Russia, mondo slavo orientale e Occidente. Storia e civiltà letteraria dal Medioevo all'epoca contemporanea" (University of Florence, April 16-17, 2015): the complexity of cultural relations between Russia, the Slavic East and the European West is analysed by enhancing the variety of points of view and by using different methodological approaches and perspectives provided by different fields of study. Here, new materials and new analytical methods are presented, useful for studying the complex interactions between the Western cultural tradition and the Eastern Slavic one from the Middle Ages to the present day. The "fractures" and "integrations" are identified through critical reading or rereading of texts, works and authors who have taken part in the construction and development of cultural relations between the different European areas.